2016
DOI: 10.1111/mcn.12353
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns by cluster analysis in pregnant women: relationship with nutrient intakes and dietary patterns in 7‐year‐old offspring

Abstract: Little is known about how dietary patterns of mothers and their children track over time. The objectives of this study are to obtain dietary patterns in pregnancy using cluster analysis, to examine women's mean nutrient intakes in each cluster and to compare the dietary patterns of mothers to those of their children. Pregnant women (n = 12 195) from the Avon Longitudinal Study of Parents and Children reported their frequency of consumption of 47 foods and food groups. These data were used to obtain dietary pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
(108 reference statements)
1
15
0
1
Order By: Relevance
“…These results suggest that consuming a nutrient dense diet during pregnancy is important for an offspring's neurological development. This is supported by our previous study (Vilela et al, 2016), which found that women in the fruit and vegetables cluster had a diet that was more nutrient dense than that of women in the other two clusters.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…These results suggest that consuming a nutrient dense diet during pregnancy is important for an offspring's neurological development. This is supported by our previous study (Vilela et al, 2016), which found that women in the fruit and vegetables cluster had a diet that was more nutrient dense than that of women in the other two clusters.…”
Section: Resultssupporting
confidence: 83%
“…It is likely that mothers' diet will influence the diet of their children once they are born. In our previous study, we found this to be the case (Vilela et al, 2016); in particular, children of mothers in the fruit and vegetables cluster were more likely than those of mothers in the other two clusters to have their diets classified in a "plant-based" cluster, which was characterised by very similar foods (Smith et al, 2011).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The first domain of this questionnaire, weight gain knowledge, has also been assessed separately in other studies. Most studies contains at least the evaluation whether women follow the guidelines to proper weight gain according to their respective weight and height [47][48][49]. In addition, our questionnaire contains items asking pregnant women whether they know that little or excessive weight gain has an impact on maternal and child's health.…”
Section: Importance Of Nutrientsmentioning
confidence: 99%